Large Language Model-Driven 3D Hyper-Realistic Interactive Intelligent Digital Human System - Yanying Song; Wei Xiong (Sensors)
Digital technologies are undergoing comprehensive integration across diverse domains and processes of the human economy, politics, culture, society, and ecological civilization. This integration brings forth novel concepts, formats, and models. In the context of the accelerated convergence between the digital and physical worlds, a discreet yet momentous transformation is being steered by artificial intelligence generated content (AIGC). This transformative force quietly reshapes and potentially disrupts the established patterns of digital content production and consumption. Consequently, it holds the potential to significantly enhance the digital lives of individuals and stands as an indispensable impetus for the comprehensive transition towards a new era of digital civilization in the future. This paper presents our award-winning project, a large language model (LLM)-powered 3D hyper-realistic interactive digital human system that employs automatic speech recognition (ASR), natural language processing (NLP), and emotional text-to-speech (TTS) technologies. Our system is designed with a modular concept and client–server (C/S) distributed architecture that emphasizes the separation of components for scalable development and efficient progress. The paper also discusses the use of computer graphics (CG) and artificial intelligence (AI) in creating photorealistic 3D environments for meta humans, and explores potential applications for this technology.